THE PSYCHIC TRUTH OF FICTION: PSYCHOANALYTIC INTERPRETATION OF DRAMA AND CHILDREN’S LITERATURE - Ivey, Gavin (PINS-Psychology in Society, 2025)
Rustin, M and Rustin, M (2001) Narratives of love and loss: Studies in modernchildren’s fiction. (2nd ed). London: Karnac (1987). ISBN: 1855752697. Pages 298. Rustin, M and Rustin, M (2002) Mirror to nature: Drama, psychoanalysis andsociety. London: Karnac. ISBN: 1855752980. Pages 289. Despite the seductive flicker of satellite television and the instantly accessible visual entertainment of computer games and DVD movies, people continue to read fiction and go the theatre. The fulfilment derived from immersion in the fictional worlds of books and the physicality of dramatic action endures, despite the technological onslaught of instant electronic gratification.